Sosialisasi Bahaya dan Cara Aman Menggunakan WiFi Publik Pada Karang Taruna Komplek Nusa Hijau - Ade Yuliana; Castaka Agus Sugianto; Novita Lestari Anggreini; Aris Haris Rismayana (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2025)
This community service aims to socialize the importance of knowing the dangers and safe use of public WiFi among Karang Taruna members in Nusa Hijau Complex. Public WiFi has become an essential part of daily life, but it also poses significant security risks. Therefore, socialization about the dangers and safe use of public WiFi is necessary to avoid these security risks. This socialization activity will be conducted through material presentation, discussion, and question-and-answer sessions. It is expected that this activity will increase the awareness and knowledge of Karang Taruna members about the importance of using public WiFi safely.